Implementation of Sanctions for Parties Who Have Not Become Members of the Social Security Implementing Board (BPJS) In Justice Perspective - Cahyani, Prilian; Astutik, Astutik; Geraldine, Agatha (Budapest International Research and Critics University, 2022)
Health care is a right that belongs to the community and an obligation that must be provided by the state. The government's effort in realizing health services is to establish the National Social Security System (SJSN). One form of SJSN is the national health insurance which is implemented by the Social Security Administering Body (BPJS). Health insurance in its implementation raises legal problems in the form of conflicts of rules. Health as a human right, requires the state to fulfill this right. The community as recipients of rights based on the principle of compulsory participation as regulated by the Law concerning the National Social Security System, is required to become a participant in social security. The result is the imposition of administrative sanctions for those who do not register as members of the BPJS. Even moment this membership Becomes BPJS members will also becomes condition in various public services such as sell buy land, management permission business and so on. The type of research used in this legal research is juridical-normative research. The approach method used is the statutory approach and the conceptual approach. Conclusion from study this is existence penalty to the party who doesn't sign up self as BPJS participants and no fulfillment right the community in public services make the government has violated the rights of its citizens.